Utilization of shrimp processing wastes in developing shrimp-flavored seasoning. - Pagador, Arianne H.
The quantity of waste generated by shrimp processing plants, which make up around 50% of the raw materials, is projected to increase along with the global expansion in shrimp production and consumption. The current study investigated the potential of shrimp processing waste as an ingredient in formulating a seasoning powder. Four formulations with varying amounts of shrimp waste powder were prepared and subjected to sensory evaluation. The results showed that the most preferred formulation was the seasoning powder incorporated with 20% shrimp waste powder. Then, the microbiological load, proximate composition, and physico-chemical properties of the shrimp waste powder and 20% shrimp-flavored seasoning powder formulation were determined. For the microbiological quality, pathogens such as E. coli, Salmonella, and S. aureus were not detected. Both powders had low total plate counts and mold and yeast counts. The proximate composition of the 20% SFSP consisted of 17.05 ± 0.81% crude protein, 2.66 ± 0.37 lipid, 10.26 ± 0.12% ash, and 7.64 ± 0.29% moisture. The values for salt content, water activity, bulk density, % solubility, and pH were 12.63 ± 0.25%, 0.46 ± 0.00, 0.50 ± 0.00 g/ml, 142.70 ± 4.00%, and 7.80 ± 0.00, respectively. The results of this study suggest that the 20% SFSP is a promising seafood product.